PREVENTION OF BULLYING AT SCHOOL AS AN EFFORT TO FORM TOUGH AND INDEPENDENT TEENAGER CHARACTER - Oktavianah, Uvi; Tiara, Putri Dwi Juniar; Puspa, Rani (International Journal of Engagement and Empowerment (IJE2), 2024)
The anti-bullying seminar held at SMPN 2 Mekar Baru aimed to enhance students' understanding of various forms of bullying, its negative impacts, and prevention efforts that can be implemented within the school environment. The seminar featured speakers from the Children's Forum and law enforcement, who provided material on types of bullying, its psychological and social effects, relevant legal policies, and applicable sanctions. The results of this event showed a significant increase in students' understanding of bullying and their willingness to report such incidents. The seminar also strengthened the synergy between schools, law enforcement, and the community in creating a safe school environment that supports the development of resilient and independent youth